The Impact of Incorporating Biochar on the Development of Goethite Nanoparticles Produced via Precipitation Method - Iwan Syahjoko Saputra; Achmad Gus Fahmi; Rifka Noor Azizah; Rina Andriyani; Anjar Hermadi Saputro; Ine Pebriyanti; Aluna Monalaika Izzati (Indonesian Journal of Science and Education, 2026)
This research explores a novel synthesis approach for goethite nanoparticles (Goe-NPs) due to the addition of biochar during goethite formation. This study investigated the effect of biochar addition on the Goe-NPs agitation process. Biochar was added on days 1, 7, 14, and 21 after reacting iron nitrate and base during agitation (30 days in 40 ℃). Based on the observation, the addition of biochar on day 14 (Goe-14d) has the smallest and most uniform particle size (±60 nm) compared to the addition of biochar on day 21 (Goe-21d) measuring about ±99 nm, and goethite synthesis without the addition of biochar (Goe-BLANK) measuring approximately >1000 nm. Functional group analysis using FTIR identifies all goethite produced from this synthesis method has an Fe-O6 octahedral lattice peak found at 642 cm-1 and Fe-O-H bending vibrations at 795 cm-1 and 889 cm-1 with varying intensity at each biochar addition time. The peak intensity of the Goe-NPs spectrum decreased when the growth of goethite particles was fully formed and agglomerated (>7 days of biochar addition). XRD analysis showed the crystal structure of Goe-NPs, with additional peaks indicating potential impurities from the formation of ferrihydrite because goethite was not fully formed. SEM images showed the effect of biochar addition on the unique particle size and morphology between Goe-NPs at biochar addition before day 7 and after day 7, indicating biochar can reduce agglomeration. This study demonstrates a promising new synthesis route for Goe-NPs using this biochar addition, with the potential to customise the size and type of goethite particles based on their growth time.